2020
DOI: 10.4236/ojce.2020.101006
|View full text |Cite
|
Sign up to set email alerts
|

Soil Stabilization Using Waste Plastic Materials

Abstract: Expansive clay soils are the types of soils whose volume changes with the change in water content. They have a behavior of swelling and shrinking that is a serious hazard to structures built over them. Expansive soils are abundantly existing soil types in Ethiopia, particularly Addis Ababa. This paper shows the outcomes of an attempt to reinforce and stabilize expansive clay soil with plastic bottle strips. The plastic strips were prepared and added at three different mixing ratios (0.5%, 1% and 2%) by weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 4 publications
4
9
0
Order By: Relevance
“…Combining shredded gloves, having a rough surface, and expansive clay could increase the stretching resistance between the particles. A similar trend was observed in previous studies on the strength properties of clay soils reinforced with plastic ( Kassa et al, 2020 ) and rubber fibres ( Yadav and Tiwari, 2017 ). However, as the SNG content was increased to 2%, the UCS reduced to 297.97 kPa, demonstrating that there is a threshold value of SNG content beyond which the UCS value decreased.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Combining shredded gloves, having a rough surface, and expansive clay could increase the stretching resistance between the particles. A similar trend was observed in previous studies on the strength properties of clay soils reinforced with plastic ( Kassa et al, 2020 ) and rubber fibres ( Yadav and Tiwari, 2017 ). However, as the SNG content was increased to 2%, the UCS reduced to 297.97 kPa, demonstrating that there is a threshold value of SNG content beyond which the UCS value decreased.…”
Section: Resultssupporting
confidence: 90%
“…The reduction in MDD can be related to the decrease in density of the mixture due to the relatively low density of shredded gloves and the decrease in compaction efficiency resulting from the elastic response of SNG. Kassa et al (2020) and Ali et al (2020) observed a similar trend by adding PET strips and PP fibres to the clayey soils, respectively.…”
Section: Resultsmentioning
confidence: 62%
“…Plastic waste has been successfully used in various studies as an additive to stabilise expansive road subgrade material. CBR value of 3.04 was achieved for soil stabilised with up to 2% plastic strip and UCS values of up to 316.4 kN were achieved [103]. Synthetic fibres such as polypropylene have been reportedly used in various studies as an additive to stabilise expansive road subgrade material.…”
Section: Effect Of Process Waste On the Engineering Properties Of Roa...mentioning
confidence: 99%
“…This soil suffers from the continuous swelling and contraction, and for this period, the engineering structures built upon it are damaged, as are road structures. [73], [74]. CKD can be added into weak soils to develop their inherent engineering properties, where CKD increase the subgrade soil texture, the shear strength and decrease the swell features [49].…”
Section: Soil Stabilization For Pavement Layersmentioning
confidence: 99%